Vaccinations for Elite Athletes - Ruuskanen, Olli; Valtonen, Maarit; Heinonen, Olli J.; Waris, Matti; Mertsola, Jussi (MDPI AG, 2026)
Elite athletes are at an increased risk of infections due to behavioral and social factors and frequent travel. Furthermore, heavy physical exercise may induce immunosuppression. Most infections in athletes are acute respiratory illnesses (ARIs) with various viral etiologies. Although athletes, as young, healthy adults, are not at risk for severe infections, a prolonged ARI may ruin a training season or a significant competition or may spread within a sports team. Many common infections are vaccine-preventable. This Opinion advocates for more active vaccination among athletes, although some of the vaccines are not officially recommended for young adults. New respiratory syncytial virus (RSV) protein vaccines are effective and well-tolerated. Yearly influenza and COVID-19 vaccinations are strongly recommended. Conjugated polyvalent pneumococcal vaccines are recommended because they may also induce protection against respiratory viral infections. Pertussis and measles outbreaks are occurring globally. The history of measles vaccination should be reviewed, and consideration should be given to a pertussis booster vaccination (Tdap). A recombinant vaccine can effectively prevent herpes zoster. The vaccination of elite athletes is a cost-effective and powerful tool, but it is currently underused. The sports medicine community can address vaccine hesitancy among athletes by listening to their concerns and giving accurate information.